Berberine-loaded M2 macrophage-derived exosomes for spinal cord injury therapy. (May 2021) - Gao, Zhan-Shan; Zhang, Chuan-Jie; Xia, Nan; Tian, He; Li, Dao-Yong; Lin, Jia-Quan; Mei, Xi-Fan; Wu, Chao
Abstract: Spinal cord injury (SCI) causes immune activation of resident macrophages/microglia. Activated macrophages/microglia have two different phenotypes, the pro-inflammatory classically activated (M1) phenotype and the anti-inflammatory alternatively activated (M2) phenotype. M1 phenotype macrophages/microglia are the key factor in inflammation. The treatment of SCI remains a huge challenge due to the nontargeting and inefficiency of anti-inflammatory drugs through the blood-brain barrier (BBB). The purpose of this experiment was to design M2-type primary peritoneal macrophages exosomes (Exos) as a drug carrier for berberine (Ber), which can be efficiently targeted to deliver drugs to the injured spinal cord due to the natural advantage of Exos across the BBB. The Exos with particle size of 125±12 nm were loaded with by an ultrasonic method and the drug loading reached 17.13 ±1.64%. The Ber release experiment showed that the loaded sample (Exos-Ber) exhibited sustained release effect, and the cumulative release amount reached 71.44±2.86% within 48 h. In vitro and in vivo experiments confirmed that the Exos-Ber could decrease the M1 protein marker iNOS, elevate the M2 protein marker CD206 and reduce inflammatory and apoptotic cytokines (TNF-α, IL-1β, IL-6, Caspase 9, Caspase 8), which showed that Exos-Ber had a good anti-inflammatory and anti-apoptotic effect by inducing macrophages/microglia from the M1 phenotype to M2 phenotype polarization. Moreover, the motor function of SCI mice was significantly improved after Exos-Ber treatment, indicating that Exos-Ber is a potential agent for SCI therapy. Statement of significance: Efficient targeting strategy for drug delivery. In addition to good biocompatibility and stealth ability, M2 macrophage-derived Exosomes present natural inflammatory targeting ability. The inflammatory microenvironment after spinal cord injury provides motivation for the targeting of exosomes. Natural drug carrier with higher safety. With the rapid development of nanomaterials, drug carriers have become more selective. However, due to the special microenvironment after central nervous system damage, some non-degradable inorganic materials will increase the pressure of self-healing and even secondary damage to neurons, which has been solved by the emergence of exosomes. Some previous studies used tumor cell line exosomes as drug carriers, but the carcinogenic factors carried by themselves have extremely high hidden dangers, and endogenous macrophage exosomes have absolute advantages over their safety. Graphical Abstract: Image, graphical abstract